Investigations on the Mode and Dynamics of Transmission and Infectivity of Borrelia burgdorferi Sensu Stricto and Borrelia afzelii in Ixodes ricinus Ticks - Crippa, Mara; Rais, Olivier; Gern, Lise (My University, 2002)
Borrelia burgdorferi sensu lato (sl), the agent of Lyme disease, is transmitted to the host during the blood meal of Ixodes ticks. In most unfed ticks, spirochetes are present in the midgut and migrate during blood feeding to the salivary glands, from which they are transmitted to the host via saliva. In the present study, the efficiency of Ixodes ricinus ticks to transmit B. afzelii and B. burgdorferi sensu stricto (ss) and their infectivity for mice were examined in relation to the duration of the blood meal. In addition, we investigated whether these two Borrelia species can penetrate intact skin. Three modes of infection of mice were studied: tick-bite infection, inoculation of tick homogenates, and transcutaneous infection by topical application of tick homogenates on mouse skin. Transmission of B. burgdorferi sl from I. ricinus nymphs to mouse increased with duration of tick attachment. B. afzelii-infected ticks start to transmit infection earlier (≤48 h) than B. burgdorferi ss-infected ticks. As previously shown for B. burgdorferi ss in Ixodes scapularis, B. burgdorferi ss and B. afzelii in unfed I. ricinus were noninfectious for mice when tick homogenates were inoculated. However, the inoculation of homogenates of ticks fed for 24 h readily produced infection in mice. Therefore, B. burgdorferi ss and B. afzelii spirochetes are potentially infectious in the tick before natural transmission can occur. None of the mice (n = 33) became infected by transcutaneous transmission when tick homogenates were applied on mouse skin, showing that B. burgdorferi ss and B. afzelii are unable to penetrate intact skin, in contrast to relapsing fever spirochetes. This study also shows that B. afzelii is transmitted by I. ricinus to the host earlier than B. burgdorferi ss and that I. ricinus seems to be a more efficient vector of B. afzelii than B. burgdorferi ss.
Keywords: Transmission; Ixodes ricinus; Borrelia burgdorferi sensu lato; Lyme borreliosis